Judul : Hubungan Faktor Personal Terhadap Tindakan Tidak Selamat Pekerja Proyek Pembangunan Gedung Di PT. X Tahun 2020 - Larasati Maulita (2021)
The number of work related accidents every year has increased. These unwanted events or work accidents were caused by 88% unsafe actions, 10% unsafe conditions, and 2% other unavoidable events. This makes the possibility of work accidents very high and can be reduced through health and safety control, in association with unsafe actions. This study aimed to determine the association between personal factors and unsafe actions. The method used was quantitative analytic with cross-sectional approach. The population of this research was workers in building construction projects and the total sample was 109 people by using the Accidental sampling method. The research instruments used were questionnaires and observation sheets. The data analysis used in this study was univariate analysis and bivariate analysis with Chi-Square Test. The results of the analysis stated that there was a significant association between personal factors, which are health and safety knowledge (p-value = 0.012), work-related fatigue (p-value = 0.018) work-related stress (p-value = 0.000), and work motivation (p-value = 0.024). Therefore, it hoped that the company can design refreshing activities for workers such as gymnastics or sports activities that have been scheduled and provide a variety of information during safety briefing.